2008
DOI: 10.1002/dmrr.808
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans urinary excretion as a marker of the early stages of diabetic nephropathy and the disease progression

Abstract: In conclusion, it can be stated that all patients with DM compared to the control group show an increase in GAG excretion independent of diabetes duration. Urinary GAG excretion positively correlates with the duration of diabetic nephropathy. The assessment of GAG excretion values may be useful for determining the early stages of diabetic nephropathy and the progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
14
2
1
Order By: Relevance
“…Most of the studies found that GAGs excretion increases as albumin excretion increases [96, 99, 100, 108, 109], two studies did not find a correlation [95, 106], and one study found a decrease in GAGs excretion as UAE increases [101]. Torffvit et al [101] found a decrease in sulphated GAGs excretion (but not of GAGs/creatinine ratio) between normoalbuminuric and albuminuric type 1 diabetic patients.…”
Section: Glycosaminoglycansmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies found that GAGs excretion increases as albumin excretion increases [96, 99, 100, 108, 109], two studies did not find a correlation [95, 106], and one study found a decrease in GAGs excretion as UAE increases [101]. Torffvit et al [101] found a decrease in sulphated GAGs excretion (but not of GAGs/creatinine ratio) between normoalbuminuric and albuminuric type 1 diabetic patients.…”
Section: Glycosaminoglycansmentioning
confidence: 99%
“…Diabetic patients with manifest nephropathy have increased urinary GAGs compared to patients with incipient nephropathy [94, 99, 108], and their sensitivity in patients with manifest nephropathy has been reported to be 100%, compared to 77% of albuminuria [99]. …”
Section: Glycosaminoglycansmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that diabetic patients excrete significantly more GAGs than the control group [32]. Moreover, increased urinary GAGs have been detected in patients with microalbuminuria or macroalbuminuria, and positively correlated with the duration of DN [33]. …”
Section: Biomarkers Of Glomerular Damagementioning
confidence: 99%
“…Diabetic patients excrete in urine significantly more glycosaminoglycans (GAGs), part of the endothelial glycocalyx, than controls 80 and such an increase has been reported in patients with all stages of albuminuria, while urinary GACs positively correlated with disease progression. 81 Moreover, several other proteins have been reported to increase in the urine of diabetic patients. Extracellular structural matrix proteins (collagen type IV, fibronectin, metalloproteinases), transforming growth factor (TGF)beta the potent inducer of extracellular matrix proteins, markers of tubular damage like the apical membrane receptors megalin and cubilin, the transmembrane protein of the apical membrane of PTCs-kidney injury molecule 1 (KIM-1), but also neutrophil gelatinase-associated lipocalin (NGAL) that is produced in the distal nephron are examples of such proteins.…”
mentioning
confidence: 99%